Effects of sacubitril/valsartan versus irbesartan in patients with chronic kidney disease: a randomised double-blind trial - Haynes, R; Judge, P; Staplin, N; Herrington, W; Storey, B; Bethel, A; Bowman, L; Brunskill, N; Cockwell, P; Hill, M; Kalra, P; McMurray, J; et al. (American Heart Association, 2018)
Background Sacubitril/valsartan reduces the risk of cardiovascular mortality among patients with heart failure with reduced ejection fraction, but its effects on kidney function and cardiac biomarkers in people with moderate-to-severe chronic kidney disease are unknown. Methods UK HARP-III was a randomised double-blind trial which included 414 participants with an estimated glomerular filtration rate (GFR) 20-60 mL/min/1.73m2 who were randomly assigned to sacubitril/valsartan 97/103 mg twice daily versus irbesartan 300 mg once daily. The primary outcome was measured GFR (mGFR) at 12 months using analysis of covariance with adjustment for each individual's baseline mGFR. All analyses were by intention to treat. This trial is registered at ISRCTN11958993. Results 207 participants were assigned to sacubitril/valsartan and 207 to irbesartan. Baseline mGFR was 34.0 (0.8) and 34.7 (0.8) mL/min/1.73m² respectively. At 12 months there was no difference in measured GFR: 29.8 (SE 0.5) among those assigned sacubitril/valsartan versus 29.9 (0.5) mL/min/1.73m2 among those assigned irbesartan; difference -0.1 (0.7) mL/min/1.73m2. Effects were similar in all pre-specified subgroups. There was also no significant difference in estimated GFR at 3, 6, 9 or 12 months and no clear difference in urinary albumin:creatinine ratio between treatment arms (study average difference -9%, 95% CI -18% to 1%). However, compared to irbesartan, allocation to sacubitril/valsartan reduced study average systolic and diastolic blood pressure by 5.4 (95% CI 3.4-7.4) and 2.1 (95% CI 1.0-3.3) mmHg, and levels of troponin I and N-terminal of pro-hormone brain natriuretic peptide (tertiary endpoints) by 16% (95% CI 8-23) and 18% (95% CI 11-25), respectively. The incidence of serious adverse events (29.5% vs 28.5%; rate ratio [RR] 1.07, 95% CI 0.75-1.53), non-serious adverse reactions (36.7% vs 28.0%; RR 1.35, 95% CI 0.96-1.90) and potassium ≥ 5.5 mmol/L (32% vs 24%; p=0.10) were not significantly different between randomized groups. Conclusions Over 12 months, sacubitril/valsartan has similar effects on kidney function and albuminuria to irbesartan, but has the additional effect of lowering blood pressure and cardiac biomarkers in people with chronic kidney disease.